2020
DOI: 10.1111/hiv.12916
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac chamber volumes and left ventricular mass in people living with HIV and matched uninfected controls

Abstract: People living with HIV (PLWH) have increased risk of cardiovascular diseases compared with uninfected populations. We assessed structural cardiac abnormalities and their associated risk factors in well-treated PLWH and uninfected controls using multidetector computed tomography (MDCT). Methods People living with HIV and age-and sex-matched uninfected controls underwent MDCT to determine left atrial volume (LAV), left ventricular diastolic volume (LVDV), right ventricular diastolic volume (RVDV) and left ventri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Despite the low prevalence of DD, PLWH in this study had higher LV mass consistent with previous echocardiogram13 21 and CT43 44 studies. In a relatively young cohort (mean age of 43 years) without history of hypertension, it is interesting to note early development of increases in LV mass potentially suggesting the role of HIV infection in the pathogenesis of these early subclinical changes.…”
Section: Discussionsupporting
confidence: 89%
“…Despite the low prevalence of DD, PLWH in this study had higher LV mass consistent with previous echocardiogram13 21 and CT43 44 studies. In a relatively young cohort (mean age of 43 years) without history of hypertension, it is interesting to note early development of increases in LV mass potentially suggesting the role of HIV infection in the pathogenesis of these early subclinical changes.…”
Section: Discussionsupporting
confidence: 89%
“…This is in contrast to some other studies who reported a higher prevalence of abnormal GLS, and cardiac dysfunction ( 11 , 28 , 35 ), but these studies were retrospective analyses of echocardiograms performed in people referred for assessment, suggesting a biased potentially symptomatic population. The studies in prospectively recruited cohorts with or without HIV-negative control groups were less likely to report clinically significant changes in GLS and other parameters of cardiac function ( 17 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, HIV was independently associated with minor reductions in LV diastolic volume. The minor differences in RV diastolic volume and LV mass were no longer significant after controlling for BSA ( 17 ). Pulmonary hypertension is also well recognised as a complication of poorly controlled HIV and ART use ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Te endocardial borders were manually traced on 15-20 tomographic slices, depending on the size of the atrial chamber. Te left atrial appendage was included in the measurement, while the pulmonary veins were meticulously excluded from the assessment of the atrial cavity [28]. LA volume index (LAVi) was calculated by dividing LA volume with body surface area (BSA), which was calculated from the Du Bois formula as follows: weight(kg) 0.425 × height(cm) 0.725 􏽨 􏽩 × 0.007184.…”
Section: Defnitionsmentioning
confidence: 99%